Issues and Challenges of Zakat Al-Mal Collection in Brunei Darussalam - Muhammad Fuad Matahir (International Journal of Zakat, 2023)
The collection of Zakāt al-Māl in Brunei Darussalam is a concern as it is still considered to be in a weak position knowing that Zakāt al-Māl collection is the main contributor to the total zakāt collected. It is known zakāt institutions faced many issues and challenges in carrying the role to improve Zakāt al-Māl collection. The main objective of this paper is to examine and elaborate the issues and challenges of Zakāt al-Māl collection in Brunei Darussalam faced by Brunei Islamic Religious Council (MUIB). This paper analyses and extracts the issues and challenges faced by MUIB from personal interviews with the head of departments in MUIB. Findings of this study indicates the issues and challenges were (1) there are limited promotions conducted by MUIB to educate the public regarding the payments of zakāt; (2) Limited number of staff; (3) The lack of using technology. This has limited the capability to improve the Zakāt al-Māl collection in Brunei in order to achieve its full potential. However, the findings also indicate there were several initiatives to tackle the issues and challenges. This paper highlights the need to promote and educate the public to increase awareness on Zakāt al-Māl payments and to utilise technology to enhance the management of zakāt especially in the collection of Zakāt al-Māl.